Bioavailability of common iron fortificants - Zhang, Jiejia (Kansas State University, 2024)
Background: Anemia was recognized by the World Health Organization as a global concern of public health and a common comorbidity of many chronic diseases. Iron fortification is one of the most cost-effective approaches to combat iron deficiency anemia. It can improve the iron status of people with iron deficiency or at the risk of iron deficiency. However, it is challenging to achieve high iron bioavailability. Thus, we conducted preclinical and clinical systematic reviews with meta-analysis and two in vitro studies to upgrade previous iron formulations for the prevention and treatment of iron deficiency anemia. Objective: To identify, evaluate, and summarize the evidence regarding the efficacy of common iron fortifications in preclinical studies and clinical trials. To assess the bioavailability of common iron fortifications in in vitro INFOGEST digestion/Caco-2 cell model. Methods: In two systemic reviews, final included articles were collected after initial articles were scanned and sorted. The characteristics of included studies were summarized for the systematic review. The data was extracted for meta-analysis. In two cell-culture studies, 20 rice or corn flour samples fortified with NaFeEDTA, ferrous fumarate, FeSO₄, FePP, or FePO₄ were digested with INFOGEST method. Subsequently, Caco-2 cells were treated with the iron digesta or iron supernatant in dual-chamber systems (dialysis membrane or insert membrane) or triple-chamber system (dialysis membrane and insert membrane) for 2 hours. The cell lysates were collected and iron bioavailability was examined by measuring ferritin concentrations. Main Results: 42 studies were included in preclinical systemic review. The data from 17 rat experiments including 52 comparisons was analyzed with pairwise meta-analysis. The results of meta-analysis showed that the overall Hb effect of NaFeEDTA was superior to that of positive control (FeSO₄). Ferrous fumarate was equivalent to FeSO₄. FePP and FePO₄ were inferior to FeSO₄. 145 studies were included in clinical systemic review. 46 studies including 88 comparisons and 24107 participants (under 18 years old) contributed to the network meta-analysis in Hb. FeSO₄, NaFeEDTA, fumarate, and FePP were more effective than placebo. The rank order of Hb effect was NaFeEDTA> ferrous fumarate> FePP> FeSO₄>electrolytic iron> placebo. In the first Caco-2 cell study (corn flour samples), the ferritins concentrations of NaFeEDTA, ferrous fumarate, and FeSO₄ in the classic dual-chamber system (dialysis membrane) were higher than those of NaFeEDTA, ferrous fumarate, and FeSO₄ in the alternative dual-chamber system (insert membrane) and the triple-chamber system. The ferritin concentrations of NaFeEDTA digesta and ferrous fumarate digesta were higher than those of NaFeEDTA supernatant and ferrous fumarate supernatant in classic dual-chamber system. NaFeEDTA had higher ferritin concentration than FeSO₄. NaFeEDTA and FeSO4 combination with low weight ratio (2:11) had higher ferritin response than NaFeEDTA and FeSO₄ combination with high weight ratio (4:9) and the NaFeEDTA and fumarate combinations. In the second Caco-2 cell study (rice flour samples), the ferritin concentrations of high ratio FePP, FePO4, and μFePP were significantly higher than those of low/zero ratio FePP, FePO4, and μFePP. Conclusions: The findings of systematic reviews and in vitro studies found that NaFeEDTA had higher bioavailability than FeSO₄. The dual-chamber system with dialysis membrane and digesta was a reliable iron bioassay. The combination of NaFeEDTA and FeSO₄ at low weight ratio had the highest bioavailability among the combination formulations. The iron bioavailability of FePP and FePO₄ was improved with high molar ratio (1:0.3:5.5) citric acid and trisodium citrate. The results of our secondary studies and primary studies on iron bioavailability were consistent.
Keywords: Iron bioavailability; Iron fortification; Systematic review; Caco-2 cell